(untitled) (Fiep Bulletin - online, 2017)
The Intensive Care Unit (ICU) was developed in the 20th century, on the need to recover / stabilize seriously wounded patients. With the increasing life expectancy, the raise on chronic diseases and high complexity treatments, as well as invasive procedures, the ICU comes with a more qualified life bearer. The ICU is the appropriate place to recoverable severe patients, who need assistance and monitoring 24 hours a day. The aim of this research is to characterize the profile of patients hospitalized in the Intensive Care Unit of a hospital in Cascavel/PR. It was a quantitative, documental study of descriptive and retrospective approach. 296 medical records were studied from January to April 2015. The observed variables in this study were gender, age, city of origin, length of stay, main causes for hospitalization, release / death. Among the main findings, there is the prevalence of males, in both cases, number of ICU admissions and number of deaths. The main cause of death for women and men was the cardiovascular diseases and expressive prevalence of elderly, representing 66.55% of total admissions. The characterization of ICU patients can aid in the guidelines of admissions and releases of this unit, as the knowledge of critical patients’ profile favors the establishment of objective criteria for this end, helping all multidiscipline team.